Tourism marketing in East and Southeast Asia - Stylidis, Dimitrios; Kim, Seongseop; Kim, Jungkeun (CABI regional tourism series, 2023)
"Despite the increased research interest in tourism in Asia, most research has focused on the key destinations the region hosts (China, Macao, Honk Kong, Thailand), neglecting others which are less well explored. As such little is known about the marketing efforts and practices along with the successes and challenges countries in the Southeast Asia sub-region have been experiencing. This book aims to address this oversight by exploring the marketing approaches, techniques and tools used by various countries in the region both collectively and individually to manage their tourism offerings and position them in the global tourism market: China, Indonesia, Japan, Korea, Macao, Mongolia, Myanmar, Vietnam.